Bipolar disorders, type 2 diabetes mellitus, and the brain. Issue 1 (January 2016) - Hajek, Tomas; McIntyre, Roger; Alda, Martin
Abstract : Purpose of review: Type 2 diabetes mellitus (T2DM) negatively affects brain structure and function. Meta-analytical data show that relative to age and sex matched non-psychiatric controls, patients with bipolar disorders have double the risk of T2DM. We review the evidence for association between T2DM and adverse clinical and brain imaging changes in bipolar disorders and summarize studies investigating effects of diabetes treatment on psychiatric and brain outcomes. Recent findings: Participants with bipolar disorders and T2DM or insulin resistance demonstrate greater morbidity, chronicity and disability, and lower treatment response to Li. Bipolar disorders complicated by insulin resistance/T2DM are associated with smaller hippocampal and cortical gray matter volumes and lower prefrontal N-acetyl aspartate (neuronal marker). Treatment of T2DM yields preservation of brain gray matter and insulin sensitizers, such as pioglitazone, improve symptoms of depression in unipolar or bipolar disorders. Summary: T2DM or insulin resistance frequently cooccur with bipolar disorders and are associated with negative psychiatric clinical outcomes and compromised brain health. This is clinically concerning, as patients with bipolar disorders have an increased risk of metabolic syndrome and yet often receive suboptimal medical care. At the same time treatment of T2DM and insulin resistance has positive effects on psychiatric and brain outcomes. These findings create a rich agenda for future research, which could enhance psychiatric pharmacopeia and directly impact patient care.